Constitutive Modelling for elevated temperature flow behaviour of AA7075. (5th July 2015) - Trimble, D.; O'Donnell, G.E.
Graphical abstract: Highlights: The flow stress of AA7075 is determined by isothermal compression tests. Prediction capability of different constitutive models is compared. Newly proposed constitutive formulation outperforms previous models. Abstract: Isothermal hot compression tests were conducted on a Gleeble-3800 mechanical simulator over a wide processing domain of temperatures (523–723 K) and strain-rates (0.001–100 s −1 ) to predict the hot deformational behaviour of AA7075 based on a number of previously used constitutive models and a newly developed empirical based constitutive model. The prediction capability of these models was evaluated in terms of average absolute relative error and correlation coefficient between predicted and experimental flow stress values. Results demonstrated that the newly proposed model can track the deformational behaviour more accurately throughout the entire processing domain investigated compared to the other models. The model recorded an average absolute relative error of 4.88% and a correlational coefficient of 0.987.